L’immagine degli italiani nella letteratura odeporica polacca del Secolo dei Lumi: i diari di Moszyński e Węgierski - Justyna Łukaszewicz; Małgorzata Ewa Kowalczyk (Diciottesimo Secolo)
The article is dedicated to two travelogues written in French by leading figures of the Polish Enlightenment such as Tomasz Kajetan Węgierski and August Fryderyk Moszyński. It aims to present and compare the portrayal of Italians conveyed by the two travellers. Węgierski toured to Italy in 1779, while Moszyński went to Italy between 1785 and 1786. The authors of this article mainly focus on the two travellers’ attitudes towards the people they met along their journeys and their observations of Italians in general as well as the inhabitants of different regions. Moszyński and Węgierski’s perception of certain aspects of Italian lifestyle and society have also been discussed in this paper. The analysis of the two journals shows that the authors were good and critical observers, who wanted to convey a subjective but realistic view of the country they visited.